O valor do cartaz: critica situacionista e design grafico - Fukushima, Kando (2007)
My goal with this Master Thesis is to contribute to the enlargement of the theoretical foundations of Design Research, as well as to point out a differentiated understanding of technology and its mediation in contemporary societies. In it, I discuss some of the concepts and practices developed by participants of the Situationist International, especially by Guy Debord, such as spectacle and détournement. Within Graphic Design, I enlist some researchers who have worked in wide critical approaches and I present a selection of contestatory posters in order to illustrate the difficulty involved in the analysis of graphic design works when everyday life is taken into account.